Internet financial crime security prevention and criminal law regulation optimization path - Xinxin, Mao; Ambaras Khan, Hanna; Ab Rahman, Suhaimi (Science Research Society, 2023)
Since the advent of the Internet, Internet and finance are becoming more and more closely integrated. In 2014, the banking industry paid around $65 billion in regulatory penalties, with misbehavior and anti-financial crime failures acting as key prosecution justifications. Many financial institutions are finding that it is difficult to properly handle growing requirements with their current processes and infrastructure, leading to significant increases in associated operational expenses. Recent improvements in data analytics, which allow a speedier analysis of larger, more thorough, and more diversified data sets, appear to have the potential to ease some of the key pain points in this context. This paper investigates the rise of Big Data in this sector, concentrating on use cases where advanced analytics is presently being applied, as well as its long-term potential.